(untitled) (Texas Journal of Philology, Culture and History, 2024)
In the realm of literature, detective fiction stands as a unique genre that not only entertains but also delves into profound reflections of the human condition. This article explores the evolution and significance of detective works in 19th and 20th-century English literature, illuminating their development, characteristics, interpretation, reception, and lasting impact.